Advancing the Impact of Critical Qualitative Research on Policy, Practice, and Science. (7th February 2022) - Shaw, James; Gagnon, Monica; Carson, Andrea; Gastaldo, Denise; Gladstone, Brenda; Webster, Fiona; Eakin, Joan
Discourses of research impact shape the ways in which critical qualitative research and researchers are evaluated in contemporary academic environments. Mainstream conceptualizations of research impact arise from a positivist perspective that challenges the aims and approaches of critical qualitative research. In this paper, we propose a framework for conceptualizing the impact of critical qualitative research on policy, practice, and science. After critiquing literature that presents mainstream views on research impact, we summarize a recent framework for conceptualizing the impact of critical research specifically. We then add to the Machen framework by highlighting the impacts of critical qualitative research on the institutions and practices of science. We provide examples of ways in which researchers at the Centre for Critical Qualitative Health Research at the University of Toronto have made contributions to the impact of critical qualitative research on science, and conclude by addressing implications of this framework for the ways in which critical qualitative researchers can plan and evidence the impact of their work.